The Compensation Decisions of the Anti-Inflation Board - Maslove, Allan; Swimmer, Gene (Relations industrielles / Industrial Relations, 1978)
This paper examines the determinants of compensation decisions of the Anti-Inflation Board during its first year of existence. A bureaucratic behavior model is developed and tested using multiple regression techniques.